The Relationship Between Motivation and Mentality towards Athletes' Psychology in Supporting Football Achievement : A Literature Study: Article Research - Munir, Ali; Nasrulloh, Ahmad; Suharjana, Suharjana; Wali, Carles Nyoman; Kerihi, Eka Citra Gayatri (Faculty of Sport and Health Sciences, 2022)
Football is a sport that is synonymous with teamwork. The nature of exercise aims to improve the various components that an athlete needs, for example physical exercise, techniques, tactics and achievements. A football athlete is not concerned with psychological factors, in this case the mental psychological factor and the motivation of the athlete. The purpose of this study was to discuss the relationship of motivation and mentality of athletes to achievement.This type of research uses literature studies. The database in this study with article criteria derived from sinta 2-5 indexed journals. The number of articles reviewed in this study totaled 4 articles with characteristics 1). Articles of the last five years, 2). The articles reviewed must be related to the focus of this research. The four articles are attached in table 1. Then the procedures for searching for the articles needed in this study are based on the Google engine: 1). Google schooler and 2). Google Chrome. The analysis of this study focused on the relationship of motivation and mentality of athletes in football achievement. The results of this study indicate that there is a relationship between mentality and athlete motivation on athlete achievement based on the results of the review. The four articles that were reviewed as a whole had positive results, that the athlete's mentality plays an important role in achieving good performance. The existence of these two psychological factors, helps athletes get maximum achievements. It is concluded that motivation and mentality affect the achievements of athletes which will have an impact on athlete performance, then athletes create maximum achievements.